Bath exhaustion on halocromic dyes - Martínez -González, Inés; Bou-Belda, Eva; Díaz-García, Pablo; Gisbert-Payá, Jaime; Bonet-Aracil, Marilés (Wydawnictwo Politechniki Łódzkiej, 2022)
Halocromic dyes change theis colour with pH. There is a problem focused on the determination of the concentration for halochromic dyes attached to a fibre. This article studies the influence of halochromism on the absorbance measurement protocol of polyamide dyeing wastewater with Rose Bengal. For this purpose, two dyes are prepared at neutral and acid pH, and their concentrations are to be determined by absorbances of exhaustion and washing wastewaters. In addition, in order to check their fastness, a washing test is carried out on dyed fabrics and on fabrics post treated with a fixer.
Keywords: Halochromism; Acid Red 94; absorbance; wavelength; dye; polyamide; absorbancja; długość fali; barwnik; poliamid